Implementation of Discharge Planning for Hospitalized Children with Tonsillitis: A Case Study - Yuzqi Rizqullah; Dicky Endrian Kurniawan; Nurfika Asmaningrum; A’Jalil Achbab (KHD Production, 2023)
Tonsillitis, especially among hospitalized children, can cause worse impacts or complications. Dynamic, planned, and patient-centered nursing care is needed, which can be done by implementing discharge planning. This study aimed to analyze and evaluate the implementation of discharge planning among hospitalized children with tonsillitis. A case study method involving one patient and his family in the pediatric inpatient room; was carried out from April 3 to 6, 2022. The results of this study show that the implementation of discharge planning has been carried out following the theory. Discharge planning is carried out when the patient enters until the patient returns with stages assessment to evaluation; besides that, from the implementation of discharge planning, there is an increase in parents' knowledge about disease and skills about the importance of a healthy lifestyle and nutrition/dietary pattern in children. This study concludes that discharge planning is important in providing nursing care because it can increase independence, knowledge, and skills in healing and maintain the patient's health status. It was needed for a more detailed discharge planning assessment format because this study only includes studies that focus on tonsillitis patients and are linked to theory. If it is implemented on patients with different diagnoses, it is necessary to update the assessment format.